Return to Sports and Physical Activities After First Metatarsophalangeal Joint Arthrodesis in Young Patients. (July 2019) - Da Cunha, Rachael J.; MacMahon, Aoife; Jones, Mackenzie T.; Savenkov, Aleksander; Deland, Jonathan; Roberts, Matthew; Levine, David; Elliot, Andrew; Kennedy, John; Drakos, Mark; Ellis, Scott J.
Background: Arthrodesis of the first metatarsophalangeal (MTP) joint has been shown to be effective in alleviating pain and correcting deformity in hallux rigidus. However, outcomes in specific sports and physical activities remain unclear. The aim of this study was to assess sports and physical activities in young patients following first MTP joint arthrodesis and to compare these results with clinical outcomes. Methods: Patients between ages 18 and 55 years who underwent MTP arthrodesis were identified by review of a prospective registry. Fifty of 73 eligible patients (68%) were reached for follow-up at a mean of 5.1 (range, 2.2-10.2) years with a mean age at surgery of 49.7 (range, 23-55) years. Physical activity was evaluated with a previously developed sports-specific, patient-administered questionnaire. Clinical outcomes were evaluated with the Foot and Ankle Outcome Score (FAOS). Results: Patients participated in 22 different sports and physical activities. The most common were walking, biking, weightlifting, swimming, running, and golf. Compared to preoperatively, patients rated 27.4% of activities as less difficult, 51.2% as the same, and 21.4% as more difficult. Patients returned to 44.6% of preoperative physical activities in less than 6 months and reached their maximal level of participation in 88.6% of physical activities. Ninety-six percent of patients (48/50) were satisfied with the procedure regarding return to sports and physical activities. Improvements in the FAOS Symptoms subscore were associated with increased postoperative running and walking duration, and improvements in FAOS Pain subscores were associated with greater patient satisfaction. Conclusion: Patients were able to participate in a wide variety of sports and physical activities postoperatively. Some patients reported increased difficulty, but were nonetheless satisfied with the procedure regarding physical activity participation. These findings suggest that first MTP joint arthrodesis is a reasonable option in young, active patients, and may be used to guide postoperative expectations. Level of Evidence: Level IV, retrospective case series.